ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KEIKUTSERTAAN MASYARAKAT DALAM PROGRAM KELUARGA BERENCANA - Wa Ode Elfianti Wahid; Ramadhan Tosepu; Asniah Asniah (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
Family planning or what is commonly referred to as family planning is a national scale program to reduce birth rates and control population growth in a country. In implementing the Family Planning program, the community should be involved in the whole process to participate. BKKBN data from North Buton Regency shows that the difference between people who participate and do not participate in the Family Planning Program is still quite large, namely in the range of 4,000-5,000 couples of childbearing age who have not participated in the Family Planning program. This study aims to describe and analyze factors related to community participation in the Family Planning program in North Buton Regency in 2022. The method used in this research is observational descriptive and analytic with a cross sectional data collection method. The results showed that of the 100 respondents who had been surveyed, there were 58 respondents who did not take part in the Family Planning Program, and there were 42 respondents who took part in the Family Planning Program. The results of the study concluded that there is a relationship between Knowledge Variables, Access to Health Services, and Family Support with Community Participation in the Family Planning Program. Meanwhile, the variables of education level, religious value, economic value, and health value have no relationship with community participation in the family planning program.